PENGARUH PROGRAM LITERASI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH KELAS XI DI SMA NEGERI 1 RENGAT - Putri, Melisa Amanda; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: SMA Negeri 1 Rengat is one of the State High Schools which was established in 1959 with Penegrian Decree No: 27 / S / B III on June 11, 1959. This study aims to determine the effect of literacy programs on student learning outcomes in class XI history learning in SMA Negeri 1 Rengat. The type of research used in this study is quantitative. This research was conducted at SMA Negeri 1 Rengat, which began from the submission of the proposal title until the completion of the thesis by the author. The subjects of this study were the students of SMA Negeri 1 Rengat, namely class XI, totaling 100 students. The analysis technique uses Simple Linear Regression with Simple Linear Correlation. The results showed the value of X (literacy program) obtained t-count of 0.795 with a significant value of 0,000. This is in accordance with the basic test criteria for decision making from the results of a simple linear correlation test that is if the significance value is less than 0.05 then it can be concluded that the hypothesis Ho is accepted, meaning that the literacy program has an effect on and significant on student learning outcomes in learning history.Key Words: The Effect of Literacy Program Against Student Learning Outcomes in LearningHistory of Class XI in SMA Negeri 1 Rengat.